FAKTOR-FAKTOR EKSTERNAL YANG MEMPENGARUHI WAKTU PEMBUAHAN MANGGIS - Irwan Darfis; Aprisal Aprisal (Jurnal Solum, 2009)
A research aiming to evaluate external factors affecting fertility process on manggo trees had been conducted in Lima Puluh Kota Regency, as one of production central for manggos in West Sumatra.  In the first year, the activity of the research was aimed to identification on earlier and later flowering plants.  External factors being identified were soil nutrients and soil chemical characteristics, as well as temperature and relative humidity around canopies of the trees.  The results showed that there was an interaction among the external factors  on the characteristics of both groups of the manggo trees.  Earlier flowering plants had higher  temperature around the canopies, but lower relative humidity than those later flowering plants.  Some other external factors such as light intensity as well as the duration of day and night period will be identified on the following research.Key Words: Manggos tree, canopy temperature and humidity, earlier flowering plants, later flowering plants